A new North Eurasian species of the Alona affinis complex (Cladocera: Chydoridae) - Sinev, Artem Y.; Karabanov, Dmitry P.; Kotov, Alexey A. (Zootaxa, 2020)
Our analysis of Alona cf. affinis (Cladocera: Chydoridae) populations from European Russia, Siberia and Far East of Russia bearing denticles at the posteroventral corner, based on both their morphology and genetic study considering variability of mitochondrial COI and 16S and nuclear 18S genes, revealed that they belong to a separate taxon described here as Alona sibirica sp. nov. Previously populations with denticles at the posteroventral corner were recorded from Sweden, Finland, Ukraine, European Russia, Kyrgyzstan and Mongolia, but never reported outside the temperate regions of Eurasia, so A. sibirica sp. nov. is presumably the only species of the A. affinis group with denticles at the posteroventral corner of the valves. The primary distribution area of the new species is North-East Palaearctic, while Eastern Europe and Central Asia are the areas of the species penetration, where it is less common and frequently coexisting with A. affinis s. str.